The Connectivity of Internal Audit and Risk Management Research - Natalia Maria Greapca; Camelia Iuliana Lungu (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- What are the dominant themes in the existing literature and future research patterns in the field of risk management and internal audit? Motivation- With the evolution of the concepts of risk management and internal audit starting from early 21st century there is a significant body of literature addressing the topic, yet a variety of gaps in the research field still remain uncovered. Idea- This paper presents a wide image of the internal audit and risk management research area, aiming to map the scientific landscape and the changing trends, using a bibliometric analysis technique extended to identify the most addressed research gaps. Data- Observing the evolving research themes in the field until early 2023, a final dataset of 246 bibliometric records were extracted from Web of Science Core Collection database. Tools- The scientific mapping analysis over the internal audit and risk management dataset is conducted using VOS viewer software. The study combines co-citation, co-occurrence of the keywords and co-words analysis of abstracts and titles in analysing the themes evolution patterns and potential future research directions. Findings- The results reveal that the research themes in the field are continuously developing, but the quantity of research output is still limited for the internal audit - risk management relationship. The main attention still lies on the effectiveness, quality and improvement in both internal audit and risk management processes. There are also other directly linked concepts with the subject area, such as corporate governance or financial reporting performance. Contribution- The current research is not without limitations; however, it may offer perspectives for future studies. The paper exposes the need for further research in the field, focusing on the interaction between internal audit and risk management, extended with factors that might moderate this relationship.
Keywords: M14; M16; M21; 650; internal audit; risk management; bibliometric analysis; science mapping; research connectivity